2013
DOI: 10.1002/cam4.149
|View full text |Cite
|
Sign up to set email alerts
|

Isocitrate dehydrogenase 2 mutation is a frequent event in osteosarcoma detected by a multi‐specific monoclonal antibody MsMab‐1

Abstract: Somatic mutations of isocitrate dehydrogenase (IDH) 1 and IDH2 occur in gliomas, acute myeloid leukemia, and cartilaginous tumors. Somatic mosaic IDH1/2 mutations are also reported in Ollier disease and Maffucci syndrome, which are characterized by multiple central cartilaginous tumors. Although IDH1/2 mutation analysis against osteosarcoma has been performed in several studies, no IDH1/2 mutation has been reported. Herein, we newly report the IDH2-R172S mutation in three of 12 (25%) osteosarcoma patients, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…Previous studies found IDH mutations in a variety of benign and malignant musculoskeletal tumors, including osteosarcomas and giant cell tumors of bone (16,31,32). Furthermore, the mouse mesenchymal cell line C3H10T1/2 expressing the IDH2 R172K mutation can give rise to poorly differentiated sarcomas in xenograft models (17).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies found IDH mutations in a variety of benign and malignant musculoskeletal tumors, including osteosarcomas and giant cell tumors of bone (16,31,32). Furthermore, the mouse mesenchymal cell line C3H10T1/2 expressing the IDH2 R172K mutation can give rise to poorly differentiated sarcomas in xenograft models (17).…”
Section: Discussionmentioning
confidence: 97%
“…Mutations in IDH1 and IDH2 frequently occur in glioma (>75%) 96 and secondary glioblastoma (GBM) (70-75%) and are rarely detected in primary glioblastoma (5%). 97,98 Mutations in IDH1 and IDH2 have also been found in various human cancers with different frequencies, including acute myeloid leukemia (AML), 99 angioimmunoblastic T-cell lymphoma, 108 Most IDH1 and IDH2 mutations in cancers are often heterozygous with a wild-type allele, 96,97,109 and the mutations have been found to result in a neomorphic enzyme activity that converts a-ketoglutarate into the R-enantiomer of 2-hydroxyglutarate.…”
Section: Isocitrate Dehydrogenase (Idh)mentioning
confidence: 99%
“…Deep sequencing further revealed that mutated IDH1 and IDH2 occur in a high proportion (>70%) of low‐grade (grade II–III) astrocytomas and oligodendrogliomas and secondary glioblastoma 51, 52, 88, 89. Since these initial reports, mutations in IDH1 and IDH2 have also been found in other diverse cancers including 16–17% of patients with AML,53 20% of patients with angioimmunoblastic T‐cell lymphomas,90 and more rarely in cholangiocarcinomas,91 breast carcinomas,92 acute lymphoblastic leukemias,93 prostate cancer,93 osteosarcoma,94 and others 53, 91, 92, 93, 95, 96, 97. Interestingly, and unlike IDH mutations in glioma which are almost entirely in IDH1 , AML have been shown to exhibit an approximately equal frequency of IDH1 and IDH2 mutations 53, 54…”
Section: Mutations Of Mitochondrial (And Associated) Metabolic Enzymementioning
confidence: 99%